Foundations for Multi-level Ontology-based Conceptual Modeling - CARVALHO, V. A. (2018)
Made available in DSpace on 2018-08-02T00:04:06Z (GMT). No. of bitstreams: 1 tese_10529_foundations_for_ontology_based_multi_level_conceptual_modeling_2012 - victorio.pdf: 6142526 bytes, checksum: 3e3483b04f4e9b86ab648e66104ac1e2 (MD5) Previous issue date: 2016-12-16